EFEKTIVITAS KOMUNIKASI BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KABUPATEN BANJAR DALAM MENGURANGI RESIKO BENCANA BANJIR DI KABUPATEN BANJAR - Hasan Baseri; Muhammad Yunus Jarmie; Deli Anhar (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
This study aims to describe how the flood of information delivered via a variety of interpersonal communication activities include socializing, discussion and drills / simulations can be understood by people in the District Pengaron and Simpang Empat.What was raised by the officers of the Regional Disaster Management Agency (BPBD) and its partners with all kinds of communication media were prepared very appealing to the public. They do play a role which is preferred when drills / simulations in the field.The symbols of communication in the form of a blue triangle emblem (symbol BPBDs). Meeting points, evacuation routes, pemantaub tool Anjir, and signs warning gong sounds in the form of code Early Warning System (EWS) and the notification of the place of worship can be understood by the people of the District and the District of Simpang Empat Pengaron Banjar district. Techniques used k omunikasi officers Regional Disaster Management Agency (BPBD) Banjar district for the provision of information through the dissemination and discussion through the Forum for Disaster Risk Reduction (DRR) Community-Based and flood disaster management practices through drills / simulations of floods in the next events.Keywords: Effectiveness Of Communication, Disaster Management and Risks